2017
DOI: 10.1186/s12864-017-3930-0
|View full text |Cite
|
Sign up to set email alerts
|

ddRADseq reveals determinants for temperature-dependent sex reversal in Nile tilapia on LG23

Abstract: BackgroundIn Nile tilapia sex determination is governed by a male heterogametic system XX/XY either on LG1 or LG23. The latter carries a Y-specific duplicate of the amh gene, which is a testis-determining factor. Allelic variants in the amh gene demonstrated to be major triggers for autosomal and temperature-dependent sex reversal. Further, QTL on LG23 and LG20 show a temperature-responsiveness with influence on the phenotypic sex relative to the sex chromosomes. Here we present a ddRADseq based approach to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…In the Nile tilapia, markers on LGs 1, 3, 20 and 23 have all been found associated with phenotypic sex in various domesticated strains [ 29 , 30 , 34 , 35 , 36 , 39 , 40 , 44 , 65 ]. To overcome possible artefacts due to the process of domestication, we have searched for the genetic basis of sex determination (SD) in wild populations of Nile tilapia and studied whether there are population differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Nile tilapia, markers on LGs 1, 3, 20 and 23 have all been found associated with phenotypic sex in various domesticated strains [ 29 , 30 , 34 , 35 , 36 , 39 , 40 , 44 , 65 ]. To overcome possible artefacts due to the process of domestication, we have searched for the genetic basis of sex determination (SD) in wild populations of Nile tilapia and studied whether there are population differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our family ddRAD results reveal that LG23 is an XY sex chromosome in both the Kpandu and Koka populations. LG23 has already been reported to be the sex chromosome in some domesticated Nile tilapia [ 41 , 43 , 44 , 65 ]. Among the significant sex-variants between 24 and 40 Mb on LG23, one is common to both populations: the anti-Müllerian hormone gene ( amh ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have applied ddRAD-seq sequencing to generate high-density linkage maps (Brown et al, 2016;Manousaki et al, 2016) and estimate genetic diversity (Antoniou et al, 2017;Hosoya et al, 2018). Furthermore, ddRADseq has been utilized in several tilapia studies for evaluating the suitability of DNA from skin mucus swabs (Taslima et al, 2017), identification of sex determining regions (Wessels et al, 2017), and quantitative trait loci (QTL) analysis (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its economic potential, the scientific community is interested in revealing the molecular mechanisms underlying economically interesting genotypes. Some traits include sexual differentiation, muscle growth, lipogenesis, and disease resistance [4][5][6][7]. Data from the plant science community have shown that economically interesting traits, such as disease resistance, biomass production, plant development, and environmental biotic or abiotic stress, can be altered by manipulation of microRNAs (miRNAs) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%